2022
DOI: 10.1111/cfs.12926
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver or care receiver: Adolescents' experience of caregiving to a parent with severe mental illness: A qualitative study

Abstract: Exploring the experiences of adolescent caregivers of mentally ill parents is essential to understand their challenges and identify their care needs. Using a qualitative research design, 18 caregiving adolescents shared their experiences of living with and providing care to a parent with a severe mental illness. The analysis of the interviews resulted in the emergence of three main categories: (1) emotional exhaustion with associated subthemes of ‘ongoing worries’, ‘fear of loneliness’, ‘feeling of shame and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Additionally, social and emotional connections may lessen the impact of mental illness in parents. 4,14,15 In fact, in this study, participants stated they thanked God their other parent was healthy, the emotional support received from siblings was very important and they coped with negative emotions with support from siblings. In research, children were reported to develop a variety of coping strategies to cope with negative feelings and understand mental illness in parents.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Additionally, social and emotional connections may lessen the impact of mental illness in parents. 4,14,15 In fact, in this study, participants stated they thanked God their other parent was healthy, the emotional support received from siblings was very important and they coped with negative emotions with support from siblings. In research, children were reported to develop a variety of coping strategies to cope with negative feelings and understand mental illness in parents.…”
Section: Discussionmentioning
confidence: 70%
“…16 However, it has been reported that the lack of support resources can harm the normal development of children/young caregivers. 15 Nurses working in community mental health should support sibling relationships when assessing families with mental illness from an integrated perspective and contribute to strengthening solidarity between siblings with this support. In this context, programs strengthening emotional support and solidarity may be included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation